Keraunoparalysis, a neurological manifestation after lightning strike: a case Report - Bajracharya, Sumana; Shrestha, Ashis; Shrestha, Sajan; Shrestha, Sitaram; Acharya, Samita; Pokharel, Yagya Raj; Amatya, Yogendra; Gauchan, Srijana; House, Rose (Journal of Patan Academy of Health Sciences, 2017)
Lightning strike can have wide range of physical and neuropsychiatric symptoms. Burn, extensive tissue damages, cardiac rhythm disturbances and secondary injuries are well described and observed. The patient may also go through transient neurological symptoms, which may go unseen in some cases while in some cases it may get extra attention and series of investigations. Keraunoparalysis is one of the immediate neurological complications encountered after lightning strike. This manifests as transient self-limiting symptoms.